Development of an e-modules for learning mathematics based on a scientific approach to help the online learning process - Selvia Erita (SAINTIS Publishing, 2022)
This study is motivated by teaching materials that are less attractive and difficult for students to understand in participating in online learning and the lack of teaching materials used in online learning, namely using only textbooks. This has an effect on student learning outcomes and students' mathematical abilities. The purpose of this study is to produce mathematics teaching materials in the form of e-modules for learning mathematics based on a scientific approach to assist the online learning process. This study is a development-research (RD). The E-module development process is carried out using the ADDIE development model. The researcher analyzed the validity and practicality of the e-modules that had been developed which were obtained through the validation results of the e-modules by the validator and the results of the questionnaire responses from mathematics teachers and students regarding the practicality of the e-modules. This e-module is declared valid based on the assessment of material experts with an average of 92% (very valid) and the assessment of media experts with an average of 75% (valid). Also, the results of the mathematics teacher's responses with an average of 85% (very practical) and the results of the student questionnaire responses with an average of 84% (very practical).